Sex-difference in the association between social drinking, structural brain aging and cognitive function in older individuals free of cognitive impairment - Abulseoud, Osama A.; Caparelli, Elisabeth C.; Krell‐Roesch, Janina; Geda, Yonas E.; Ross, Thomas J.; Yang, Yihong (Frontiers in Psychiatry, 2024)
Background: We investigated a potential sex difference in the relationship between alcohol consumption, brain age gap and cognitive function in older adults without cognitive impairment from the populationbased Mayo Clinic Study of Aging. Methods: Self-reported alcohol consumption was collected using the food-frequency questionnaire. A battery of cognitive testing assessed performance in four different domains: attention, memory, language, and visuospatial. Brain magnetic resonance imaging (MRI) was conducted using 3-T scanners (Signa; GE Healthcare). Brain age was estimated using the Brain-Age Regression Analysis and Computational Utility Software (BARACUS). We calculated the brain age gap as the difference between predicted brain age and chronological age.The sample consisted of 269 participants [55% men (n=148) and 45% women (n=121) with a mean age of 79.2±4.6 and 79.5±4.7 years respectively]. Women had significantly better performance compared to men in memory, (1.12±0.87 vs 0.57±0.89, P<0.0001) language (0.66±0.8 vs 0.33±0.72, P=0.0006) and attention (0.79±0.87 vs 0.39±0.83, P=0.0002) z-scores. Men scored higher in visuospatial skills (0.71±0.91 vs 0.44±0.90, P=0.016). Compared to participants who reported zero alcohol drinking (n=121), those who reported alcohol consumption over the year prior to study enrollment (n=148) scored significantly higher